Microstrip Rectangular Monopole Antennas with Defected Ground for UWB Applications - S. Elajoumi; A. Tajmouati; A. Errkik; Am. Sanchez; M. Latrach (Institute of Advanced Engineering and Science, 2017)
This paper presents the design of new compact antennas for ultra wide band applications. Each antenna consists of a rectangular patch fed by 50Ω microstrip transmission line and the ground element is a defected ground structure (DGS). The aim of this study is to improve the bandwidth of these antennas by using DGS and the modification geometry of rectangular structure, which gives new compact antennas for UWB applications. The input impedance bandwidth of the antennas with S11<-10dB is more than 10GHz, from 3GHz to more than 14 GHz. The proposed antennas are investigated and optimized by using CST microwave studio, they are validated by using another electromagnetic solver Ansoft HFSS. The measured parameters present good agreement with simulation. The final antenna structures offer excellent performances for UWB system.